Root and tuber crops in Nevis - Lowery, J.E. (International Center for Tropical Agriculture, 1986)
The 4 main starchy root crops grown in Nevis (sweet potato, yam, cocoyam, and cassava) are described regarding production, wholesale and retail prices, and domestic and external demand. Cassava is grown on a small scale, almost exclusively for home use. It is planted as an alternative to leaving the land fallow; therefore the most common planting time is between Jan.-March, coinciding with the dry season. Silba pendula is the most important pest, but no control measures are applied. The yield level calculated by the Caribbean Agricultural Research and Development Institute is of 1596 kg/ha. It is recommended that any cassava research be directed toward livestock feed rather than human consumption. (CIAT)